Bodies that speak: Languages of differentiation and becoming in Amazonia. (November 2018) - High, Casey
Abstract: In this article I consider the metaphysical underpinnings of a specific language ideology in Amazonian Ecuador by comparing Waorani ideas about the agency of speech in shamanism and funerary practices to their engagements in language documentation. I relate the notion of language as a force inseparable from the bodies of speakers to concepts of language as "culture" in research to document their language. By considering how Waorani consultants have come to see certain features of their language in video recordings, such as sound symbolism, I examine the differences and interconnections between Waorani language ideology and multiculturalist understandings. These interactions suggest divergent ontologies at the same time as they demonstrate how indigenous people operate simultaneously within contrasting imaginings of differentiation. Highlights: The affective properties of language demonstrate the inseparability of body and voice in Waorani understandings of becoming. Amazonian people operate simultaneously within contrasting regimes of differentiation. Collaborative projects illustrate contrasting ideas about the nature of language in Amazonia social dynamics.